Optimization of an innovative hydrothermal processing on prebiotic properties of eucheuma denticulatum, a tropical red seaweed - Birdie Scott Padam; Chee Kiong Siew; Fook Yee Chye (2022)
Seaweed is a sustainable source of marine oligosaccharides potentially could be used as a prebiotic ingredient for the functional food development. The study aims to optimize the oligosaccharide preparation through thermal hydrolysis of an under-utilized red seaweed, Eucheuma denticulatum. Response Surface Methodology (RSM) applying the Box-Behnken Design (BBD) was used on three parameters including temperature (105ºC-135ºC), hydrolysis time (15-35 min) and sulfuric acid concentration (0.05-0.2M). Optimized fractions with good prebiotic activity were characterized using HPLC-SEC and FT-IR. Oligosaccharides fraction ED-F1 was shown to promote the growth of beneficial gut microbiota including Lactobacillus plantarum, L. casei, L. acidophilus, Bifidobacterium animalis and B. longum with the highest prebiotic activity score of 1.64±0.17. The optimization studies showed that hydrolysis time was the most significant parameter for the oligosaccharides yield. Optimal hydrolysis conditions for ED-F1 were 120ºC, 21 min, 0.12M H2SO4 with the highest yield achieved (11.15 g/100 g of dry weight). Molecular weight of ED-F1 was determined at 1025 Da while FT-IR analysis revealed the presence of sulfated oligosaccharides with similar characteristics of i-carrageenan. These findings signify the innovative method for the efficient production of seaweed derived prebiotic oligosaccharides, which could be a promising source of functional food ingredients for the development of health foods and beverages.